PENGAWASAN INSPEKTORAT DAERAH PROVINSI RIAU TERHADAP PERANGKAT DAERAH DI KOTA PEKANBARU TAHUN 2020-2021 - Femillya Putri Feraz; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Supervision is monitoring and observing activities, behavior, and information with the aim of gathering information, influencing, overshadowing and directing. The Riau Provincial Inspectorate is an element of regional government supervisory which in carrying out its duties is directly responsible to the Governor through the Regional Secretary, and has the task of assisting the Governor in fostering and supervising the implementation of government affairs which are the authority of the region. However, the supervision carried out by the Riau Regional Inspectorate is still considered not optimal for Regional Apparatuses in Pekanbaru City. This study aims to find out what form of supervision is carried out by the Riau Regional Inspectorate on Regional Apparatuses in Pekanbaru City in 2020-2021 and to find out what factors influence the supervision carried out by the Riau Regional Inspectorate on Regional Apparatuses in Pekanbaru City. The method used in this research is descriptive method with qualitative research. The types of research data are primary data and secondary data. The data analysis technique used is descriptive qualitative data analysis. By using the Theory of Bureaucratic Functions according to Michael G. Roskin namely Administration Functions, Service Functions, Regulatory Functions and Information Gathering Functions. The results of this study are that there is supervision carried out by the Regional Inspectorate of Riau Province against Regional Apparatuses in Pekanbaru City in 2020-2021 which refers to the Governor of Riau Regulation Number 73 of 2020 Concerning Position, Organizational Structure, Duties and Functions, and Work Procedures of the Riau Regional Inspectorate to be precise in article 3 point (b) in which the implementation of the supervision carried out has not been optimal seen from the lack of performance of the Regional Apparatuses in Pekanbaru City. As well as factors that influence supervision in this regard are Human Resources (HR), Leadership, the lack of physical field data, and the lack of coordination between institutions and agencies/services. Keywords: Bureaucratic Function, Supervision